2020
DOI: 10.1515/reveh-2020-0096
|View full text |Cite
|
Sign up to set email alerts
|

Environment as the risk factor for tuberculosis in Malaysia: a systematic review of the literature

Abstract: ObjectiveTo investigate the prevalence and incidence of TB by focusing on its environmental risk factor in Malaysia.ContentDatabases search of Scopus, ScienceDirect, PubMed, Directory of Open Access Journals (DOAJ), Cumulative Index to Nursing and Allied Health Literature (CINAHL) Plus, MyJournal, Biblioteca Regional de Medicina (BIREME), BioMed Central (BMC) Public Health, Medline, Commonwealth Agricultural Bureaux (CAB), EMBASE (Excerpta Medica dataBASE) OVID, and Web of Science (WoS) was performed, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This finding confirms the results of previous studies. 19,20 Individuals living in areas with inadequate house density are more likely to develop tuberculosis due to high levels of contact, thereby accelerating the transmission of the virus if a family member has tested positive. The SDGs call for adequate housing to minimize the spread of infectious diseases, including tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding confirms the results of previous studies. 19,20 Individuals living in areas with inadequate house density are more likely to develop tuberculosis due to high levels of contact, thereby accelerating the transmission of the virus if a family member has tested positive. The SDGs call for adequate housing to minimize the spread of infectious diseases, including tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] High contact in crowded settlements and poor ventilation also increase the risk of TB transmission. 19,20 Previous studies have identified other risk factors, including family history of infection, poor waste management and access to clean water. 21 Early observations in the Medan Tembung area showed an increase in the number of cases over the last 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…But an important subject is the widespread occurrence of drug-resistant TB (DR-TB, worries around DR-TB are growing in current years. At least 5% of whole universal cases of TB have several types of drug resistance, that is, resistance to, as a minimum, one first-line anti-TB drug [ 19 22 ].…”
Section: Risk Factors For Mycobacterium Tuberculosis ...mentioning
confidence: 99%
“…In terms of environmental controls, unsafe indoor environments in high congregate settings, and overcrowding in general, are most critical ( 7 ). Finally, respiratory protection is focused on reducing TB transmission to health workers, people attending health care facilities, or people in other settings with a high risk of transmission ( 6 ).…”
Section: Introductionmentioning
confidence: 99%